Indigenous nutrient supply and fertilizer use efficiency in rainfed lowland rice in eastern Uganda - Kyalo, Gerald; Chemining’wa, George; Apunyo, Peter Charles; Nhamo, Nhamo; Wanyama, Ibrahim; Mussgnug, Frank (Frontiers in Agronomy, 2025)
The yields and supply of rice have continuously remained low despite increase in demand. A study was carried out using Randomized Complete Block Design to determine the indigenous nutrient supply (INS) of lowland rice soils and the nutrient use efficiency of fertilizer in order to develop a site specific nutrient management option for eastern Uganda. Indigenous nutrient supply was determined by the omission plot technique using five treatments; control (no fertilizer), NPK, PK (-N), NK (-P) and NP (-K) with NPK rates of 58.2 kg N ha-1, 13.2 kg P ha-1 and 49 kg K ha-1. A total of 27 omission experiments were set up over a two-year period with each farmer acting as a replicate.The grain yield ranged from 1.1- 8.7 t ha-1 with the mean of 3.8 t ha-1. The full NPK treatment yielded significantly higher than PK and control treatments (NPK plots= 4.83 t ha-1). The yield in NPK treatment was 73, 40, 23 and 25% higher than control, PK (-N), NK (-P) and NP (-K) treatments, respectively. There was no significant difference between treatments for agronomic efficiency of N.The mean RE was 31% N, 9.9% P and 59% K with NPK treatment recording an average RE for N of 46.9%. The RE for P was low at 19% (for NPK), 9.9% (for control and NK), 9.3% for NP and 1.4 for PK. Average IUE was 36.9 kg grain kg−1 N, 270 kg grain kg−1 P and 28 kg grain kg−1 K, respectively. The average indigenous nutrient supplies for nitrogen (INS), phosphorus (IPS) and potassium (IKS) were 52, 9.7 and 87.2 kg ha–1, respectively. The Gross return over fertilizer cost (GRF) for the full NPK treatment was $1,275.3 ha–1 with gains of $270 ha-1 when compared to the control. The calculated respective N, P and K doses were 63, 12.6 and 24.5 kg ha–1 indicating a saving of 49, 74 and 59% on applied NPK respectively. This study has shown that fertilizer use in eastern Uganda is profitable and SSNM has demonstrated big savings on fertilizer N, P and K.